2020
DOI: 10.1002/cnm.3298
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale subvoxel perfusion model to estimate diffusive capillary wall conductivity in multiple sclerosis lesions from perfusion MRI data

Abstract: We propose a new mathematical model to learn capillary leakage coefficients from dynamic susceptibility contrast MRI data. To this end, we derive an embedded mixed‐dimension flow and transport model for brain tissue perfusion on a subvoxel scale. This model is used to obtain the contrast agent concentration distribution in a single MRI voxel during a perfusion MRI sequence. We further present a magnetic resonance signal model for the considered sequence including a model for local susceptibility effects. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Hence, a homogeneous distribution of the leaked interstitial GBCA is likely to exhibit T1 dominant signal behaviour, while a compartmentalised/heterogeneous distribution, favours T2* effects. [20] The positive-negative dichotomy to the interpretation of K2 values that we underscore among PCNSL, GBM, and Mets borrows from the work of Liu et al [11] 2…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hence, a homogeneous distribution of the leaked interstitial GBCA is likely to exhibit T1 dominant signal behaviour, while a compartmentalised/heterogeneous distribution, favours T2* effects. [20] The positive-negative dichotomy to the interpretation of K2 values that we underscore among PCNSL, GBM, and Mets borrows from the work of Liu et al [11] 2…”
Section: Discussionmentioning
confidence: 85%
“…GBCA induced T1 relaxivity changes are microscale effects, that stem from T1 shortening of protons adjacent to the GBCA molecule. In contrast, T2* relaxivity changes result from superposition of mesoscale field perturbations induced by susceptibility gradients across tissue compartment interfaces [20]. Hence, a homogeneous distribution of the leaked interstitial GBCA is likely to exhibit T1 dominant signal behaviour, while a compartmentalised/heterogeneous distribution, favours T2* effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we identify four major areas of research at the tissue scale (shown in Figure 4 ) and discuss the modeling strategy or strategies applied to these areas. Broadly, these areas include: (1) representing the evolving geometry of the tumor’s vascular network (panel a in Figure 4 ) [ 29 , 82 , 87 , 88 , 119 , 120 , 121 , 122 , 123 ], (2) estimating the associated blood flow and vascular transport of substances (panel b in Figure 3 ) [ 81 , 88 , 122 , 123 , 124 , 125 , 126 , 127 ], (3) describing the mechanisms underlying the complex interplay between tumor growth and vasculature dynamics (panel c in Figure 4 ) [ 32 , 81 , 87 , 88 , 121 , 123 , 128 , 129 ], and (4) determining the effect of cytotoxic, targeted, and anti-angiogenic therapies on the tumor-associated vascular network as well as the tumor itself (panel d in Figure 4 ) [ 28 , 85 , 86 , 124 ].…”
Section: Approaches For Modeling Tumor Vasculature and Angiogenesis At The Tissue Scalementioning
confidence: 99%
“…The modeling of vascular flow usually includes a description of flow in the blood vessels, along with its coupling with flow in the tissue through a mass flux at the capillary walls or at the terminal ends of larger vessels. Similar to the cell-scale models reviewed in Section 3 , these phenomena can be modeled by discrete [ 33 , 87 , 88 , 122 , 123 , 126 , 130 , 131 , 132 ], continuous [ 128 , 129 , 133 , 134 ], or hybrid [ 127 , 135 , 136 ] approaches. In discrete vascular models both the pre-existing and the angiogenic vasculature are frequently approximated by a 1D network of connected straight cylinders with the flow in each cylinder simulated using the 1D Poiseuille law [ 33 , 87 , 88 , 122 , 123 , 126 , 130 , 131 , 132 ].…”
Section: Approaches For Modeling Tumor Vasculature and Angiogenesis At The Tissue Scalementioning
confidence: 99%
See 1 more Smart Citation